Hierarchical clustering of PI3K and MAPK pathway proteins in breast cancer intrinsic subtypes. Issue 4 (27th February 2020) - Kruger, Dinja T.; Opdam, Mark; Sanders, Joyce; van der Noort, Vincent; Boven, Epie; Linn, Sabine C.
Abstract : The phosphatidylinositol‐3‐kinase (PI3K) and mitogen‐activated protein kinase (MAPK) pathways are frequently activated in breast cancer. We recently demonstrated the importance of analyzing multiple proteins as read‐out for pathway activation in ER+/HER2− breast cancer, since single proteins are known to provide insufficient information. Here, we determined pathway activation in other primary breast cancer intrinsic subtypes derived from postmenopausal patients. Tumor blocks were recollected, and immunohistochemistry was performed using antibodies against PTEN, p‐AKT(Thr308), p‐AKT(Ser473), p‐p70S6K, p‐4EBP1, p‐S6RP(Ser235/236) and p‐ERK1/2, followed by unsupervised hierarchical clustering. In 32 ER+/HER2+, 37 ER−/HER2+ and 74 triple‐negative breast cancer patients, subgroups were identified with preferentially activated ( A ) and preferentially not activated ( N ) proteins. These subgroups likely reflect tumors with differences in biological behavior as well as treatment outcome.